REPRESENTASI PRIMORDIALISME DALAM FILM DOKUMENTER “SEDEKAH KA BUMI” KARYA WATCHDOC - Yowana Fadhilah (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
Indonesia is a country with a multicultural society, which has led to the emergence of various customs or belief systems, traditions, and different social structures. The documentary film